A Plant Extract Nanoparticles as a Strategy Against MRSA: A Literature Review: Nanopartikel Ekstrak Tanaman sebagai Strategi Melawan MRSA: Sebuah Kajian Literatur - ANDIKA WAHYU WARDANA; LARYSA FERNENDA; ANGGA KURNIAWAN (Jurnal Ilmu Kesehatan Abdurrab, 2026)
Methicillin-Resistant Staphylococcus aureus (MRSA) is a global health threat that requires joint prevention and control. MRSA exhibits bacterial resistance to most antibiotics, thereby increasing mortality, morbidity, costs, and length of hospital stay. Natural ingredients can be used as a new strategy to deal with this global problem because of their unique content and low toxicity. Nanoparticles have become a popular and innovative technology with various advantages and potential to be utilized in the development of new drugs, especially antibacterial resistance therapy. Therefore, this study provides general knowledge about previous studies of plant extract nanoparticles and their activity against MRSA, so that they can be considered as adjuvant therapy to support the effectiveness of conventional antibiotics. The search method for scientific journals as references is carried out through the science direct database, google scientist, and PubMed as well as manual searches with the keywords “nanoparticle”, “extract”, “plant”, and “MRSA” based on inclusion and exclusion criteria. Nanoparticles have various types and their synthesis methods, which have been carried out by various previous studies to fight MRSA. This study succeeded in demonstrating its antibacterial activity against MRSA strains based on the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values. In addition, this study is also able to summarize various previous studies that show the high potential of herbal plants as adjuvant therapy against MRSA.